Advanced Liver Steatosis Accompanies an Increase in the Level of Colonic Pro-inflammatory Bile Acids and Hepatic Inflammation in C57BL/6 Mice Fed a High-fat Diet (P15-027-19). (13th June 2019) - Zeng, Huawei; Larson, Kate; Cheng, Wen-Hsing; Bukowski, Michael; Safratowich, Bryan; Hakkak, Reza
Abstract: Objectives: The gut-liver axis is implicated in the pathogenesis of liver diseases; however, the mechanistic link between the gut and fatty liver disease severity remains to be characterized. We tested the hypothesis that advanced liver-steatosis accompanies an increase in the concentrations of colonic proinflammatory bile acids and hepatic inflammation in mice fed a high fat (HF) diet. Methods: Four-week-old male C57BL/6 mice ( n = 14/group) were fed a HF (45% energy fat) or a low-fat (LF) (10% energy fat) diet for 21 wks. We used biochemical, immunohistological, gas & liquid chromatography with mass spectrometry, RNA sequencing and real-time PCR methods to examine the level of colonic proinflammatory bile acids and hepatic inflammation. Results: At the end of the study, body weight and body fat percentage in the HF group were 0.23- and 0.41- fold greater than the LF group, respectively. Compared with the LF group, the HF group exhibited an increase in hepatic lipid droplets, inflammatory cell infiltration, inducible nitric oxide synthase, and hepatocellular ballooning cells (without hepatic Mallory bodies) which are key histological features of advanced hepatic steatosis. Furthermore, nicotinamide n-methyltransferase and selenoprotein P, two hepatic proinflammation-related genes, were upregulated in the HF group. With unique colonic bile acid profiles, the levels of colonic hydrophobic (secondary) bile acids (lithocholic acids and deoxycholic acids) were at least 0.5- fold greater in the HF group compared with the LF group. It is known that these hydrophobic bile acids induce proinflammatory cytokine production (TNF-α and IL-6) in the colon, and exacerbate hepatic inflammation via portal venous circulation. This potential colon-liver axis is consistent with results that the plasma concentrations of TNF-α and IL-6 were 0.5-fold greater in the HF group compared the LF group. Conclusions: Our results demonstrate that advanced liver-steatosis accompanies an increase in colonic proinflammatory bile acid levels and hepatic inflammation, which suggests a cross-talk between colon and liver in mice fed a HF diet. Funding Sources: This work was funded by the US Department of Agriculture, Agricultural Research Service, CRIS project 3062-51000-050-00D.